Acupuncture Enhances Dorsal Raphe Functional Connectivity in Knee Osteoarthritis With Chronic Pain - Gao, Nan; Shi, Haiping; Hu, Sheng; Zha, Bixiang; Yuan, Aihong; Shu, Jianhua; Fan, Yinqiu; Bai, Jin; Xie, Hongyu; Cui, Jingcheng; Wang, Xiaoxiao; Li, Chuanfu; et al. (Frontiers in Neurology, 2022)
Introduction Knee osteoarthritis is a common disease in the elderly. Patients suffer from long-term chronic pain and reduced life quality. Acupuncture has been proven to be an effective treatment for KOA. However, the neural mechanism of acupuncture is unclear, so far. Periaqueductal gray (PAG) and raphe nuclei (RPN) are essential structures associated with chronic pain in human brains. This study aims to investigate functional connectivity (FC) changes of PAG and RPN in KOA to interpret the neural mechanism of acupuncture. Methods In 15 patients with KOA and 15 healthy controls (HC), we acquired Visual Analog Scale (VAS) scores and resting-state fMRI images of each participant before and after acupuncture stimulation on EX-LE5 acupoint. Then, PAG and RPN were selected as seeds to perform FC analysis based on resting-state fMRI images. Finally, we compared FC patterns of PAG and RPN between patients with KOA and HC, then between pre-acupuncture and post-acupuncture. Correlations between FC values and VAS scores were calculated as well. Results For PAG, FC of patients with KOA was lower in the right lingual gyrus at post-acupuncture compared with HC (p <0.001, uncorrected). For dorsal RPN, FC of patients with KOA was significantly higher in right putamen at post-acupuncture compared with HC (p <0.001, corrected with FDR), and FC changes were significant between pre-acupuncture and post-acupuncture in patients with KOA. Post-acupuncture FC values between dorsal RPN and right putamen were correlated with VAS scores. For medial RPN, FC of patients with KOA was lower in the right cerebellum at post-acupuncture compared with HC (p <0.001, uncorrected), but no significant FC changes were found between pre-acupuncture and post-acupuncture in patients with KOA. FC values between medial RPN and right cerebellum were not correlated with VAS scores at pre-acupuncture and post-acupuncture. Discussion Our study demonstrated that acupuncture enhanced FC between dorsal RPN and the right putamen in patients with KOA, which was associated with chronic pain intensity. This result suggests that acupuncture stimulation can enhance FC between dorsal raphe and striatum, illustrating a neural mechanism that acupuncture can drive the patients' brain, with KOA, to perceive pain.